Simultaneous nitrate and perchlorate removal from groundwater by heterotrophic-autotrophic sequential system - TURANLI, BESTE; BEREKETOĞLU, CEYHUN (ELSEVIER SCI LTD, 2017)
Perchlorate is a naturally occurring and manufactured chemical anion and can be present in water sources together with nitrate. This study aims at (1) determining the nitrate and perchlorate contamination in a semi-arid plain (Harran Plain) and (2) evaluating the performance of a heterotrophic-autotrophic sequential denitrification process for nitrate and perchlorate removal from the groundwater of this plain. The nitrate in the groundwater samples varied between 4.07 and 83.22 mg l(-1) NO3--N. Perchlorate was added to groundwater samples externally and its concentration was increased from 100 to 1500 mu g l(-1). The total nitrogen concentrations in the sequential system effluent throughout the study were always below 0.5 mg l(-1). C/N ratio was 2.44 which was slightly lower than the theoretical level of 2.47. Therefore the average NO3--N in the heterotrophic reactor effluent was 19 +/- 3.7 mg l(-1) corresponding to an efficiency of 75% reduction. The remaining nitrate and nitrite were almost completely reduced in the autotrophic process. The system's perchlorate removal efficiency was above 98%, except during the last period (82%), at which influent perchlorate was 1500 mu g l(-1). The maximum perchlorate reduction rate throughout the study was around 15 mg/(L.d). Both perchlorate and nitrate reduction were partial in the heterotrophic reactor, but completed in the following autotrophic process. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Groundwater quality; Nitrate reduction; Perchlorate reduction; Sequential system; MIXOTROPHIC DENITRIFICATION PROCESSES; DRINKING-WATER; HARRAN PLAIN; GAP PROJECT; REDUCTION; IRRIGATION; RATIO; TIME